Time-Out Method for Developing Social Sensitivity in Children Aged 5–6 Years - Lokita Purnama Sari; Akaat Hasjiandito (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study examines how the time-out method is implemented to support the development of social sensitivity among children aged 5–6 years at TK Islam Nurul Wathon. Using a qualitative descriptive case study design, data were collected through participant observation, semi-structured interviews, and documentation involving one child as the main subject and one classroom teacher as the primary informant, selected through purposive sampling. The findings suggest a gradual improvement in the child's sharing behaviour and turn-taking skills during the implementation of the time-out method. Supporting factors included teacher consistency and peer cooperation, while inhibiting factors included inconsistent parenting patterns and classroom spatial limitations. The study implies that time-out, when implemented as a reflective and educative strategy, can contribute to fostering prosocial behaviour in the observed early childhood classroom context. Further research is recommended to replicate this study in different educational contexts with larger and more diverse participants.